Diuron metabolites and urothelial cytotoxicity: In vivo, in vitro and molecular approaches - Da Rocha, Mitscheli S. [UNESP]; Arnold, Lora L.; Dodmane, Puttappa R.; Pennington, Karen L.; Qiu, Fang; Camargo, João Lauro Viana de [UNESP]; Cohen, Samuel Monroe [UNESP] (Elsevier B.V., 2013)
Diuron is carcinogenic to the rat urinary bladder at high dietary levels. The proposed mode of action (MOA) for diuron is urothelial cytotoxicity and necrosis followed by regenerative urothelial hyperplasia. Diuron-induced urothelial cytotoxicity is not due to urinary solids. Diuron is extensively metabolized, and in rats, N-(3,4-dichlorophenyl)urea (DCPU) and 4,5-dichloro-2-hydroxyphenyl urea (2-OH-DCPU) were the predominant urinary metabolites; lesser metabolites included N-(3,4-dichlorophenyl)-3-methylurea (DCPMU) and trace levels of 3,4-dichloroaniline (DCA). In humans, DCPMU and DCPU have been found in the urine after a case of product abuse. To aid in elucidating the MOA of diuron and to evaluate the metabolites that are responsible for the diuron toxicity in the bladder epithelium, we investigated the urinary concentrations of metabolites in male Wistar rats treated with 2500 ppm of diuron, the urothelial cytotoxicity in vitro of the metabolites and their gene expression profiles. DCPU was found in rat urine at concentrations substantially greater than the in vitro IC50 and induced more gene expression alterations than the other metabolites tested. 2-OH-DCPU was present in urine at a concentration approximately half of the in vitro IC50, whereas DCPMU and DCA were present in urine at concentrations well below the IC50. For the diuron-induced MOA for the rat bladder, we suggest that DCPU is the primary metabolite responsible for the urothelial cytotoxicity with some contribution also by 2-OH-DCPU. This study supports a MOA for diuron-induced bladder effects in rats consisting of metabolism to DCPU (and 2-OH-DCPU to a lesser extent), concentration and excretion in urine, urothelial cytotoxicity, and regenerative proliferation. (C) 2013 Elsevier Ireland Ltd. All rights reserved.
Keywords: Bladder; Diuron; Metabolites; Cytotoxicity; Rat; In vitro